Strategi Efektif dalam Manajemen Konflik Studi Kasus di Organisasi Modern - Nurul Hikmah; Nofiyatus Sya’ada; Firman Hakiki; Mu’alimin Mu’alimin (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Conflict in organizations is an unavoidable phenomenon, especially in organizations that have dynamic and complex work environments. This study aims to identify and analyze effective conflict management strategies in modern organizations. Case studies were conducted in several organizations with different work structures and cultures. The approaches used in this study include negotiation, mediation, collaboration, and context. The results show that effective strategies depend on the characteristics of the conflict, the role of the leader, and open communication between the parties involved. Technology plays an important role in facilitating conflict resolution, especially in modern organizations that are increasingly digitally connected. These findings are expected to provide guidance for managers and organizational leaders in designing more effective conflict management strategies, increasing productivity, and creating a harmonious work environment.